(untitled) (Revista Internacional de Ingeniería de Estructuras, 2023)
In this paper, the seismic vulnerability of 74 housing located at 13 city blocks in the urban center of Siltepec, Chiapas, Mexico, have been assessed. For this purpose, two methods are used: 1) the typological classification according to the European Macro Seismic Scale (EMS-98) and 2) the Vulnerability Index Method (VIM) of RISK-UE. The latter is a refined method of the first which quantifies the construction factors in a better way and the behavior of every building which directly affect the estimation of their vulnerability. The results obtained are presented in seismic vulnerability tables and maps, and it is shown that, in the studied area, there are High Vulnerability Class Buildings (B) and Very High Class (A). It is observed that the seismic vulnerability assessment, according to the EMS scale criteria, is significantly improved when applying the VIM which perceives an increase in Class A constructions (from 26 to 44) and a decrease in Classes B (from 26 to 20) and C (20 to 10) according to the EMS evaluation.